1990
DOI: 10.1111/j.1475-4754.1990.tb00462.x
|View full text |Cite
|
Sign up to set email alerts
|

Islamic Glass Weights and Stamps: Analysis Using Nuclear Techniques

Abstract: A non‐destructive bulk analytical method based on instrumental neutron activation techniques was developed to study Islamic glass weights and stamps. Three different successive irradiations are necessary. A calibration method and a calculation program have been developed in order to correct both the different observed interferences and geometrical factors. A good relationship was formed between the chronological classification of the objects and the compositional groups.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
75
0
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 118 publications
(79 citation statements)
references
References 3 publications
3
75
0
1
Order By: Relevance
“…Only 10 samples belonging to this N2-a2 type have been identified from the Raya site. They are, at the present stage, not subdivided such as the published data of Foy et al (2003) and Gratuze and Barrandon (1990). Glass objects with a low lime composition similar to this N2-a2 type were found from the primary glassmaking sites in the Wadi Natrun (Nenna et al, 2005).…”
Section: N2-a Type (Low Ca High Ti Fe)mentioning
confidence: 61%
See 2 more Smart Citations
“…Only 10 samples belonging to this N2-a2 type have been identified from the Raya site. They are, at the present stage, not subdivided such as the published data of Foy et al (2003) and Gratuze and Barrandon (1990). Glass objects with a low lime composition similar to this N2-a2 type were found from the primary glassmaking sites in the Wadi Natrun (Nenna et al, 2005).…”
Section: N2-a Type (Low Ca High Ti Fe)mentioning
confidence: 61%
“…Their chemical compositions are slightly different from the N2-a2 type objects in that the HIMT glass objects contained manganese oxide at around 1.0-2.5 wt% (Freestone et al, 2005), while our N2-a2 type objects contained less than 0.1 wt% (Table 1). This low lime and high alumina composition corresponds to the chemical composition of the Groups 8 and 9 characterized by Foy et al (2003), Groups 1a and 1b characterized by Gratuze and Barrandon (1990) and the Egypt I type characterized by Freestone et al (2000) as shown in Fig. 6(b).…”
Section: N2-a Type (Low Ca High Ti Fe)mentioning
confidence: 71%
See 1 more Smart Citation
“…Egypt 1 glass is generally associated to early Islamic primary production in the area of Wadi Natrun because of the analysis of well dated 7the8th century Islamic weights from that region (Gratuze and Barradon, 1990). This link is also supported by the work of Sayre et al (Sayre and Smith, 1973) who analysed four Egyptian weights dated between AD 719 and AD 781, a chalice found at Wadi Natrun and a sample from a kiln from the same location, both of uncertain date.…”
Section: Himt and Hlimt: Similar Names Different Primary Productionsmentioning
confidence: 98%
“…It also enables to recognize idiosyncratic distribution networks and, consequently, to reconstruct trade routes. At the current state of research, scholars have identified five major compositional groups distributed over the Empire between the 4th and the 7th century AD: Levantine 1, Levantine 2 (Freestone and Hughes, 2000), Egypt 1, Egypt 2 (Gratuze, 1988;Gratuze and Barradon, 1990) and HIMT (i.e. High Iron Manganese Titanium) (Mirti et al, 1993;Freestone, 1994).…”
Section: Introductionmentioning
confidence: 98%